The interpretation of academic integrity in the universities of Mexico and Spain - Cancelo-Sanmartín, Mercedes; Rodríguez-Segura, Leticia; Budar-López, Enrique Jaime (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Higher education centres are spaces for the generation of knowledge, derived from this, the application of the primary values that govern academic and scientific development is linked. Among these underlying values such as honesty, justice, respect, responsibility, and trust. There are multiple interpretations of academic integrity, this study promotes which covers all the elements mentioned as basic values of social and university development: honesty, justice, respect, responsibility, and trust. This study is aimed at knowing the degree of transparency, commitment, and integrity present in universities in the development of their academic and research work.